Meningkatkan Prestasi Belajar Matematika Materi Pecahan Sederhana melalui Metode CTL - Andi, andiwapa (Balai Diklat Keagamaan Denpasar, 2024)
This research focuses on efforts to improve Mathematics learning outcomes in simple fraction modules through contextual teaching learning methods for class II students at SDN Karangnangka 1. This research aims to find out whether contextual teaching learning procedures can have a better impact on student learning outcomes. This educational improvement research is classroom action research which was attempted at Karangnangka 1 with a total of 31 students. The application of this research was attempted through 2 cycles consisting of planning, implementation, observation and reflection stages. The research results show the results of the Mathematics formative test in the pre-cycle with the percentage of students who have not reached the KKM of 77.42%, and the remaining 22.58% have reached the KKM. In cycle I there was an increase in the percentage of students who had reached the KKM by 64.52%, and 35.48% had not yet reached the KKM. In cycle II, 93.55% of students had reached the KKM, and the remaining 6.45% had not yet reached the KKM. Based on these results, it can be concluded that there has been an increase in learning outcomes through the Contextual Teaching Learning method using teaching aids in class II at SD Negari Karangnangka 1